Pengaruh Profesionalisme Aparat Kelurahan Terhadap Kualitas Pelayanan Publik (Suatu Studi di Kecamatan Mapanget Kota Manado) - Ilahude, Febriani; Pesoth, willy; Tampongangoy, Deysi Livi (Sam Ratulangi University, 2015)
Abstract: The performance of public service bureaucracies become increasingly strategic policy issue, due to improved performance of the bureaucracy has broad implications in the economic life of politics. In economic life, improved performance of the bureaucracy will be able to affect the investment climate are necessary to accelerate development in the region.This research was conducted in order to more mengetehui researchers more about the influence of the apparatus profisionalisme village on the quality of public services in order to increase development in the community.Research methods can be grouped according to purpose, approach, level of explanation and data types. In keeping with the focus of the research is professionalism and quality of public services in the district Mapanget Manado City, this research is more likely if the level of explanation using descriptive research method, with quantitative research approaches.Key Words : Proffesionalism Aparrature, Public Services